BINDING OF NORMALS OF THE SECOND GENUS OF THE TANGENTIALLY DEHENTIATED SURFACE OF NON-Euclidean SPACE - Гребенюк, М. Ф. (Proceedings of National Aviation University (archive), 2021)
The differential geometry of tangentially degenerate surfaces of non-Euclidean space is considered.